A study on the distribution of interleukin-10 gene polymorphisms and their association with febrile seizure susceptibility in children from the Wenzhou region, Zhejiang Province - Lu, Liqiang; Huang, Heng; Ding, Zhenyao; Lin, Ziliang; Lv, Xinsheng; Gan, Tianjie (Frontiers in Public Health, 2025)
BackgroundFebrile seizures (FS) were the most common seizure disorder in young children, with a notable prevalence in the Zhejiang Province region of China. The pathogenesis of FS involves both genetic and environmental factors, particularly the role of cytokines like Interleukin-10 (IL-10), an anti-inflammatory agent. This study examines the distribution of IL-10 gene polymorphisms and their association with FS susceptibility in children from Wenzhou, Zhejiang Province.MethodsThis retrospective study included 77 pediatric patients with FS and a control group of 71 healthy children. The FS group was divided into simple FS (SFS) and complex FS (CFS) subgroups. IL-10 gene polymorphisms at loci 1,082 (rs1800896 G/A), 819 (rs1800871 C/T), and 592 (rs1800872 A/C) were analyzed. IL-10 expression levels were measured, and association with FS susceptibility was evaluated using statistical methods including logistic regression.ResultsIL-10 expression levels were significantly reduced in children with FS (mean: 3.42 ± 1.27 pg./mL) compared to controls (mean: 3.87 ± 1.16 pg./mL; p = 0.027). The 1082 (rs1800896) AA genotype was more prevalent in the FS group (44.16%) versus controls (26.76%; p = 0.039). Similarly, the 592 (rs1800872) AA genotype was more frequent in the FS group (33.77%) than in controls (14.08%; p = 0.014). In CFS cases, the AA genotype of rs1800896 was significantly prevalent (58.33% compared to 31.71% in the SFS group; p = 0.044). A strong negative correlation was found between IL-10 levels and FS risk (rho = −0.175, p = 0.034), supporting findings from logistic regression that showed higher IL-10 levels were protective (OR = 0.525, p = 0.018).ConclusionReduced IL-10 levels and specific IL-10 gene polymorphisms, particularly rs1800896 and rs1800872, were associated with increased susceptibility to febrile seizures in children from Wenzhou. These findings may inform early diagnostic markers, risk stratification tools, and potentially guide personalized treatment strategies for children at higher risk of FS.